Inside the Black Box: Identifying the Variables That Mediate the Effects of an Experimental Intervention for Adolescents. (March 2015) - Hay, Carter; Wang, Xia; Ciaravolo, Emily; Meldrum, Ryan C.
In recent decades, researchers have identified many programs that successfully reduce juvenile delinquency. Evaluations of these programs generally do not, however, assess the mediating variables that intervene between program participation and reduced delinquency. Thus, although much insight has been gained on which programs are effective, the question of why they are effective is often neglected. This study addresses this issue by considering the risk factors that mediate the effects of a comprehensive intervention on juvenile offending. This was considered with data from the Children at Risk program, a 2-year multimodal intervention with random assignment that has been shown to reduce delinquency among high-risk early adolescents.